Identification of microbial airborne contamination routes in a food production environment and development of a tailored protection concept using computational fluid dynamics (CFD) simulation. (December 2022) - Zand, Elena; Brockmann, Gerrid; Schottroff, Felix; Zunabovic-Pichler, Marija; Hartmann, Anne; Kriegel, Martin; Jaeger, Henry
Abstract: Airborne microbial re-contaminations are among the most frequent causes of food spoilage, contributing to food waste and economic losses. Cleanrooms can help to avoid bioaerosol re-contaminations, but are not suitable for open food processing environments. The present study assessed airborne microbial levels and their contamination routes within bakery production. Current airborne mold and total viable counts (TVCs) were evaluated over 8 months, indicating mold and TVCs ranging from 20 to 960 CFU/m 3 and from 20 to 1600 CFU/m 3, respectively. The relative contamination level of each source point towards the cooling zone was virtually reproduced. The overall aim of this study was to develop a tailored cost-effective and easy-to-apply partial protection strategy, based on filter fan units (FFUs). The FFU concept with an air velocity of 0.3 m/s resulted in a significant reduction of the relative contamination (99.94%). Hence, this study suggests an alternative FFU-based control strategy for airborne contaminations within open food processing areas. Highlights: Evaluation of microbial counts in a bakery production facility. Investigation of airborne microbial transmission routes through numerical simulation. Identification of (bio)aerosol carryover by passive scalar transport functions with computational fluid dynamics. Reduction of airborne contamination (≤99.94%) by targeted filter fan unit protection strategy.